2018
DOI: 10.1016/j.idcr.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

First confirmed case of human rabies in Saudi Arabia

Abstract: HighlightsFirst confirmed case of human rabies in Saudi Arabia reported.Epidemiology of rabies with emphasis on its potential to spread across borders from high to low prevalence countries has been discussed.Potential for spread of rabies from animals to humans has been highlighted.Need for more uniform travel guidelines with more consensus globally among different countries has been stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…The Kingdom of Saudi Arabia (KSA) is the largest country in the Arabian Peninsula, yet there is little information about its rabies situation. During the period 2007–2009, the Saudi Ministry of Health reported more than 11,000 human bite cases [ 32 ]. The majority of animal bites were from dogs (50%) and cats (26.7%), with rodents and camels playing a minimal role [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kingdom of Saudi Arabia (KSA) is the largest country in the Arabian Peninsula, yet there is little information about its rabies situation. During the period 2007–2009, the Saudi Ministry of Health reported more than 11,000 human bite cases [ 32 ]. The majority of animal bites were from dogs (50%) and cats (26.7%), with rodents and camels playing a minimal role [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the period 2007–2009, the Saudi Ministry of Health reported more than 11,000 human bite cases [ 32 ]. The majority of animal bites were from dogs (50%) and cats (26.7%), with rodents and camels playing a minimal role [ 32 ]. A seasonal difference was reported in the occurrence of bites.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in the case presented here, the chief complaint of chest pain deviated the medical team's attention/focus away from a diagnosis of rabies to heart disease. Though uncommon, such cases have been reported ( Table 2) [4][5][6][7][8] , since rabies can caused focal interstitial myocarditis as discussed by Park et al 9 In the case series reported by Mani et al 10 , all cases presented without evidence of chest pain, so the clinical presentations of rabies vary. Furthermore, concerning the classical sign of fear of water, in our case, the patient 11 In terms of the forensics aspect, since a rabies investigation is not performed on every case with an unknown cause of death examined by only external examination, the forensic physician thought of rabies infection as the cause of death based on the review of the history recorded on the first emergency room visit and the numerous dogs observed by the forensic physician at the crime scene during the post-mortem visit at the patients residence.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these facts, there are very few studies available, and no case of human rabies has been reported in recent decades from Saudi Arabia [40]. However, in March 2018, a scientific work was reported as the first confirmed case of human rabies in Saudi Arabia from Makkah City, which has now been published [41]. Indeed, several previous global epidemiological data confirmed that rabies accounted for 24,000 to 60,000 human deaths per year [42], and more than 40% of these cases occur in children < 15 years of age [43].…”
Section: Viral Zoonosesmentioning
confidence: 99%
“…His past medical history was significant for hypertension and diabetes type 2. During the clinical diagnostic procedure of this case, he developed respiratory distress and tachycardia, for which he was transferred to the intensive care unit [41]. Because, his case worsened with chest pain and ventricular tachycardia he was referred to the King Abdullah Medical City in Makkah for further management.…”
Section: Viral Zoonosesmentioning
confidence: 99%